Characteristics of infertile couples in Santiago de Cuba - Guillermo Mora García; Jacqueline María Baquero Suárez; Maité González García; Maribel Vaillant Rodríguez (Centro Provincial de Información de Ciencias Médicas, 2019)
Introduction: The incidence of infertility has increased and, according to expert doctors and diverse specialized organizations, a clear relationship exists between the system of current life and the decrease of fertility. Objective: To characterize the infertile couples according to selected clinical-epidemiological variables. Methods: An observational, descriptive and cross-sectional study of 132 infertile couples assisted in the Infertility Service and Assisted Reproduction of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital, was carried out during 2018. Results: A high number of women were older than 40 years (32.2%), as long as, seven percent of the studied couples was diagnosed with secondary infertility and thirty three point three percent presented nicotine addiction, with prevalence in the male sex. Conclusions: The age of women, sexually transmitted infections and history of previous abortions could be the main causes of infertility in Santiago de Cuba.